Neurological disorders in case of spice poisoning. What “the first contact physician” need to know? (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
The article describes pharmacological characteristics of modern designer drugs outgoing from the group of hallucinogenic spices;the mechanisms of action, and clinical manifestations of intoxication are considered, focusing on neurological consequences which determination is helpful in speeding up the diagnosis, before managing the toxscreen. The possibilities of pharmacological approaches in spices poisoning are discussed. The results of investigation of cholinergic and adenosinic medications in amelioration of adrenergic syndrome and complications and druginduce psychosis also is presented. spice.